Investigating EFL Learners’ Autonomous Use of Vocabulary Learning Strategies Outside of School: English - Ruswandi, Riki; Vini Tenisa Aprilianti, Zalsa; Fitri Utami, Ulfah (Universitas Hamzanwadi, 2024)
As communication in English relies on a robust vocabulary, high school learners must now take responsibility for independently mastering vocabulary through effective learning strategies driven by the shift toward promoting learner autonomy in modern teaching methods. Therefore, this study examines the vocabulary learning strategies that English as a Foreign Language (EFL) learners use autonomously outside of school and the factors that influence their strategy choices. This qualitative study utilizes questionnaires and semi-structured interviews involving 66 eleventh-grade students from Istiqamah High School in Bandung, Indonesia, who completed the questionnaires and 4 of whom participated in the interviews. The results of this study reveal that learners exhibit a moderate level of autonomy and use vocabulary learning strategies at a moderate level. Metacognitive strategies are the most frequently employed, followed by determination, affective, social, compensation, memory, and cognitive strategies. The study also highlights several factors that influence learners' awareness of the importance of autonomy and the use of vocabulary learning strategies, including gender—where males tend to show higher levels of autonomy and strategy use—age, with 18-year-olds demonstrating higher autonomy and 17-year-olds more actively using vocabulary strategies, and motivation, driven by personality, goal achievement, and the desire to improve language skills. Personal consistency in learning also emerged as a critical factor in learners' success in improving their vocabulary. This research implies that students may benefit from focusing on metacognitive strategies as a practical approach to learning vocabulary in English.